2022
DOI: 10.3390/s22145413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Rolling Bearing Fault Samples in New Conditions: A Framework Based on a Modified CGAN

Abstract: Bearings are vital components of rotating machines that are prone to unexpected faults. Therefore, bearing fault diagnosis and condition monitoring are essential for reducing operational costs and downtime in numerous industries. In various production conditions, bearings can be operated under a range of loads and speeds, which causes different vibration patterns associated with each fault type. Normal data are ample as systems usually work in desired conditions. On the other hand, fault data are rare, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The proposed XAI framework can be effectively applied to assess the synthetic samples made by GAN models. This paper includes a detailed evaluation of the Conditional Generative Adversarial Network (CGAN) introduced by [37]. Their work brings forth a unique data augmentation approach tailored to fault data synthesis.…”
Section: Application Ii: Evaluating Generative Modelsmentioning
confidence: 99%
“…The proposed XAI framework can be effectively applied to assess the synthetic samples made by GAN models. This paper includes a detailed evaluation of the Conditional Generative Adversarial Network (CGAN) introduced by [37]. Their work brings forth a unique data augmentation approach tailored to fault data synthesis.…”
Section: Application Ii: Evaluating Generative Modelsmentioning
confidence: 99%
“…The effectiveness of the approach is demonstrated through a case study in aerospace shell parts spinning, showcasing precise root cause identification and determination of intervention degree. To further delve into the field of causal discovery in manufacturing and condition monitoring, a comprehensive review can be found in [23] and [24].…”
Section: Causal Discovery In Manufacturing Industrymentioning
confidence: 99%
“…Bearings, as common components in the industrial field, are also crucial parts of rotating machinery. About 44% of machine failures in the industrial field are related to bearing faults [1]. Therefore, research on bearing anomaly detection is essential.…”
Section: Introductionmentioning
confidence: 99%